ANALISIS CITRAAN DALAM BUKU KUMPULAN PUISI “LILIN” KARYA WIWID WINARISIH DENGAN PENDEKATAN OBJEKTIF - Laia, Septian Ester Tegar Wati (Universitas Nias Raya, 2025)
The problem in this research lies in visual imagery because it discusses too much visual imagery, resulting in a lack of other imagery variants. This research was motivated by the researcher's curiosity about the imagery in Wiwid Winarsih's poetry collection